التنمر وعلاقته بالسلوك العدواني لدى المراهق المتمدرس في مرحلة الثانوي دراسة ميدانية لحالات بثانوية زغبة الدراجي بالمسيلة - رقية رايس; سلوى عريوة; اشراف: حمزة خوجة (جامعة محمد بوضياف -المسيلة, 2025)
تهدف هذه الدراسة إلى الكشف عن العلاقة بين التنمر والسلوك العدواني لدى المراهقين المتمدرسين في مرحلة التعليم الثانوي. وقد تم استخدام المنهج الوصفي التحليلي، واستُعمل استبيان لجمع البيانات من عينة من تلاميذ الثانوي. أظهرت النتائج وجود علاقة قوية بين التنمر والسلوك العدواني، حيث أن التلاميذ الذين يمارسون التنمر غالبًا ما يظهرون سلوكًا عدوانيًا واضحًا في تعاملهم مع الآخرين. كما تبين أن الذكور أكثر ممارسة للتنمر من الإناث، وأن ضعف المتابعة الأسرية والرقابة المدرسية يساهم في تفشي هذه الظاهرة. خلصت الدراسة إلى ضرورة تكثيف جهود التوعية داخل المؤسسات التربوية، وتفعيل دور الأخصائي النفسي والاجتماعي، إضافة إلى تعزيز التعاون بين الأسرة والمدرسة للحد من السلوك العدواني المرتبط بالتنمر. الكلمات المفتاحية: التنمر- السلوك العدواني- المراهقة - المتمدرس- التعليم الثانوي Study summary: This study aims to explore the relationship between bullying and aggressive behavior among adolescents in secondary education. Bullying is a recurring aggressive behavior practiced by a student against their peers, taking various forms, including verbal, physical, psychological, and even electronic. A clinical approach (case study) was used, and a questionnaire was used to collect data from a sample of secondary school students. The results showed a strong relationship between bullying and aggressive behavior, as students who engage in bullying often display clear aggressive behavior in their interactions with others. It was also found that males are more likely to engage in bullying than females, and that weak family follow-up and school supervision contribute to the spread of this phenomenon. The study concluded that awareness-raising efforts within educational institutions should be intensified, the role of psychological and social specialists should be activated, and cooperation between families and schools should be strengthened to reduce the aggressive behavior associated with bullying. Keywords: Bullying – Aggressive behavior – Adolescence – School student – Secondary education